Heather, the totality - Weiner, Matthew 1965- (Canongate, 2017)
The Breakstone family arrange themselves around their daughter Heather, and the world seems to follow: beautiful, compassionate, entrancing, she is the greatest blessing in their lives of Manhattan luxury. But as Heather grows - and her empathy sharpens to a point, and her radiance attracts more and more dark interest - their perfect existence starts to fracture. Meanwhile a very different life, one raised in poverty and in violence, is beginning its own malign orbit around Heather
Keywords: Suspense fiction; Thriller; krimi; Fiktionale Darstellung